THE IMPLEMENTATIONOF STUNTINGHANDLING POLICY IN GORONTALO REGENCY LIMBOTO HEALTH CENTER - lisnawaty bakari; Muhammad Isman Jusuf; Adnan Malaha (LP2M Universitas Bina Mandiri Gorontalo, 2021)
This research aims to 1) know the implementation of stunting handling policies in Gorontalo Regency Limboto Health Center. 2) know the factors that affect the implementation of stunting handling policies in Gorontalo Regency Limboto Health Center. The results showed that 1) Implementation of stunting treatment policies in Limboto Health Center Gorontalo regency has been going well, specific nutritional intervention activities with the target of pregnant women, specific nutritional intervention activities with the target of breastfeeding mothers and children under 6 months of age, Specific nutritional intervention activities with the target of breastfeeding mothers and children aged over 6 to 23 and sensitive nutrition intervention activities with community targets, in handling Stunting in Limboto Health Center Gorontalo regency have all gone well. 2) Human resources in terms of quantity that needs to be addressed are the number of human resources available, it is necessary to add human resources so that there is no double position and the quality of human resources quality is good in accordance with their respective competencies.The obstacle is that cross-program communication is not optimal because sometimes there are village midwives who are not present for communication to break up and affect the acceleration of stunting handling. In addition, there are differences in the number of stunting data in each village. Sometimes the overall number of stunting sufferers is not known by midwives as the person in charge of the village. The solution is to improve more effective communication related to handling stunting to be an inhibitory factor in implementation, while disposition and bureaucratic structure become factors supporting the implementation of stunting handling policies in Gorontalo Regency Limboto Health Center.